Natural killer (NK) cells augment atherosclerosis by cytotoxic-dependent mechanisms. (26th January 2014) - Selathurai, Ahrathy; Deswaerte, Virginie; Kanellakis, Peter; Tipping, Peter; Toh, Ban-Hock; Bobik, Alex; Kyaw, Tin
Abstract: Aim: Although natural killer (NK) cells, a key component of the innate immune system, have been identified in human and mouse atherosclerotic lesions, their role in atherosclerosis development remains unclear. To determine their role in atherosclerosis, we used both loss- and gain-of-function experiments in ApoE −/− mice fed a high-fat diet. Methods and results: Treatment of ApoE −/− mice with anti-Asialo-GM1 antibodies depleted NK cells without affecting other lymphocytes, including natural killer T cells, and greatly attenuated atherosclerosis. These effects were independent of plasma lipids. To confirm the atherogenicity of NK cells, these cells were isolated from mouse spleens for adoptive transfer into lymphocyte-deficient ApoE −/− Rag2 −/− IL2rg −/− mice. Transfer of NK cells from wild-type mice into ApoE −/− Rag2 −/− IL2rg −/− mice doubled lesion size, confirming a pro-atherogenic role for NK cells. To determine whether their atherogenicity was dependent on production of interferon-γ (IFN-γ) or cytotoxins, we compared the transfer of NK cells deficient in IFN-γ, perforin, and granzyme B with the transfer of wild-type NK cells. Transfer of IFN-γ-deficient NK cells increased lesion size in the lymphocyte-deficient ApoE −/− mice as wild-type NK cells. However, granzyme B- and perforin-deficient NK cells did not affect lesion size. Only wild-type NK cells increased necrotic core size, whereas perforin- and granzyme B-deficient NK cells did not. Plasma lipid levels were largely unaffected by the cell transfer. Conclusion: Our loss- and gain-of-function findings provide definitive evidence that NK cells are atherogenic and their production of perforin and granzyme B contributes to atherosclerosis and the expansion of necrotic cores.